The State of Governance at State-owned Enterprises - Wong, Simon C.Y. (International Finance Corporation, Washington, DC, 2018)
Commercial enterprises that are owned and controlled by governments continue to constitute a significant portion of business activity in many parts of the world. This paper examines three critical areas for strengthening the quality of governance of state-owned firms professionalizing government ownership, strengthening commercial orientation, and developing stronger, more independent boards and the challenges involved in implementing reforms.